The universalist tendency in the mirror of a «Islamic-Christian» icon of Tatáritsa, Bulgaria - Spasova Ilieva, Vladislava (’Ilu. Revista de Ciencias de las Religiones, 2017)
The supraconfessional spirit, very characteristic of the Ottoman world, which tended to regroup many different elements, and was based on the universal conviction, according to which all religions are valued and competed for the same purposes, still resonates in the Balkans. A significant example, that in this article is analyzed from the perspective of the phenomenon of shared holiness and as a mirror of diverse influences, is an icon of Bulgaria, the unusual Islamic-Christian representation of the Virgin and Child, which was recently located in a village where, apart from the «Turks» and Bulgarians, there are still living descendants of the Don Cossacks, who are ethnically Russian.